2009
DOI: 10.2174/156802609789753653
|View full text |Cite
|
Sign up to set email alerts
|

The Identification, Characterization and Optimization of Small Molecule Probes of Cysteine Proteases: Experiences of the Penn Center for Molecular Discovery with Cathepsin B and Cathepsin L

Abstract: During the pilot phase of the NIH Molecular Library Screening Network, the Penn Center for Molecular Discovery focused on a series of projects aimed at high throughput screening and the development of probes of a variety of protease targets. This review provides our medicinal chemistry experience with two such targets -cathepsin B and cathepsin L. We describe our approach for hit validation, characterization and triage that led to a critical understanding of the nature of hits from the cathepsin B project. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…2528 Both in vivo and in vitro studies have demonstrated that certain cathepsin B inhibitors reduce tumor cell motility and invasiveness. 29,30 Because of these links, considerable effort has been made to identify cathepsin B inhibitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2528 Both in vivo and in vitro studies have demonstrated that certain cathepsin B inhibitors reduce tumor cell motility and invasiveness. 29,30 Because of these links, considerable effort has been made to identify cathepsin B inhibitors.…”
mentioning
confidence: 99%
“…The system is applied to cathepsin B, a cysteine protease implicated in tumorigenesis, arthritis, and parasite infection. Both in vivo and in vitro studies have demonstrated that certain cathepsin B inhibitors reduce tumor cell motility and invasiveness. , Because of these links, considerable effort has been made to identify cathepsin B inhibitors. Successful inhibitors include epoxysuccinyl, aziridinyl, biguanide, and β-lactam derivatives. , The MS screen used here reveals several potential new inhibitors.…”
mentioning
confidence: 99%
“…However, no orally bioavailable, brain effecting, cathepsin B-specific inhibitor is currently available and developing such will be difficult and will take considerable resources and time. For example, a high throughput screen of the National Institutes of Health (NIH) small molecule library for a cathepsin B-specific inhibitor did not find a druggable hit ( 309 ). The known cathepsin B-specific inhibitor, CA-074, is not orally druggable and when made more so with the addition of a methyl group, it looses specificity.…”
Section: E64d Is a Promising Drug Inhibitor Of Cathepsin B For Preclimentioning
confidence: 99%
“…They are viewed as potentially useful drug targets, as their catalytic activity can be inhibited by small molecules that have become an attractive field for the pharmaceutical industry [24][25][26][27]. Cathepsin L is a lysosomal protease that is the main catalyst in intracellular protein catabolism, is associated with atherosclerosis, metabolic syndrome and cancer, and has also been related to bone resorption, sperm cell maturation, macrophage malfunction and Alzheimer's disease [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%